2023
DOI: 10.3389/fnetp.2023.1205476
|View full text |Cite
|
Sign up to set email alerts
|

Modifying functional brain networks in focal epilepsy by manual visceral-osteopathic stimulation of the vagus nerve at the abdomen

Hendrik Lehnertz,
Timo Broehl,
Thorsten Rings
et al.

Abstract: Non-invasive transcutaneous vagus nerve stimulation elicits similar therapeutic effects as invasive vagus nerve stimulation, offering a potential treatment alternative for a wide range of diseases, including epilepsy. Here, we present a novel, non-invasive stimulation of the vagus nerve, which is performed manually viscero-osteopathically on the abdomen (voVNS). We explore the impact of short-term voVNS on various local and global characteristics of EEG-derived, large-scale evolving functional brain networks f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Recently, Lehnertz et al (2023a) reported on a similar reconfiguration and modification of networks together with their stability and robustness properties in a group of 20 subjects with and without epilepsy upon a short-term manual visceral-osteopathic stimulation of the vagus nerve at the abdomen. This finding may add to the current discussion on the importance of the gut-brain axis in the treatment of epilepsy ( Ding et al, 2021 ; Sinha et al, 2022 ) and to further enhance our understanding of how multiple organs in the human body dynamically interact as a network and integrate their functions to generate (patho-)physiological states ( Ivanov, 2021 ).…”
Section: The Time-evolving Epileptic Brain Network: What Have We Lear...mentioning
confidence: 98%
“…Recently, Lehnertz et al (2023a) reported on a similar reconfiguration and modification of networks together with their stability and robustness properties in a group of 20 subjects with and without epilepsy upon a short-term manual visceral-osteopathic stimulation of the vagus nerve at the abdomen. This finding may add to the current discussion on the importance of the gut-brain axis in the treatment of epilepsy ( Ding et al, 2021 ; Sinha et al, 2022 ) and to further enhance our understanding of how multiple organs in the human body dynamically interact as a network and integrate their functions to generate (patho-)physiological states ( Ivanov, 2021 ).…”
Section: The Time-evolving Epileptic Brain Network: What Have We Lear...mentioning
confidence: 98%
“…Indeed, the use of causal indices based on mathematically more sophisticated methods may provide further insights and should be the focus of future research in the field. Most importantly, because the field of network physiology is still developing with application in various diseases (Berner et al., 2022 ; dos Santos et al., 2022 ; Hall et al., 2024 ; Legault et al., 2024 ; Lehnertz et al., 2023 ; Rizzo et al., 2023 ) and scenarios including in sports and sleep analysis among others (Antonacci et al., 2023 ; Difrancesco et al., 2023 ; Ganglberger et al., 2023 ; Mangalam et al., 2024 ; Marsh et al., 2023 ; Sides et al., 2023 ), the methods available for detecting physiological connectivity as well as for quantifying such connectivity will depend on the nature of the research question being assessed, the type, quality, and quantity of data available as well as the technical repertoire at the disposal of researchers.…”
Section: Limitationsmentioning
confidence: 99%
“…The osteopathic medicine (OM) approach involves manual treatment of the peripheral and cranial nerves and autonomic systems directly and indirectly. A recent article demonstrated a change in the response of the vagus nerve in patients with epilepsy, working the area of parasympathetic abdominal innervation (in indirect mode and not with the hands on the nerve) [ 10 ]. OM to release mechanical tensions at the level of the occipitomastoid suture, where the jugular foramen and the exit of the vagus nerve (and glossopharyngeal and accessory nerves) are present, allows to improve the systemic parasympathetic response [ 11 ].…”
Section: Introductionmentioning
confidence: 99%